2012
DOI: 10.1039/c2em30405h
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent aqueous dispersibility of carboxylated multiwall carbon nanotubes

Abstract: The size dependent colloidal behavior of aqueous dispersions of carboxylated multiwall carbon nanotubes (c-MWCNTs) is presented. The presence of carboxylic groups provided electrostatic stabilization in water, where the size affected agglomeration. While aspect ratio did not show any definite correlation, the hydrophobicity indices (HI), zeta potential and aggregation kinetics showed dependence on the length of the c-MWCNTs where the shorter c-MWCNTs showed significantly lower HI values, smaller particle aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
(53 reference statements)
1
24
0
Order By: Relevance
“…An increase in CNT aggregation with increasing salt concentration and counterion valence consistent with the DLVO theory and the Schulze-Hardy rule and has been reported previously (Elimelech et al 1998, Ntim et al 2012). Time-resolved dynamic light scattering (TRDLS) has been extensively used to determine the aggregation behavior of diverse nanoparticles in the presence of salts, organic matter, and biological materials (Ntim et al 2012).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…An increase in CNT aggregation with increasing salt concentration and counterion valence consistent with the DLVO theory and the Schulze-Hardy rule and has been reported previously (Elimelech et al 1998, Ntim et al 2012). Time-resolved dynamic light scattering (TRDLS) has been extensively used to determine the aggregation behavior of diverse nanoparticles in the presence of salts, organic matter, and biological materials (Ntim et al 2012).…”
Section: Resultssupporting
confidence: 88%
“…Time-resolved dynamic light scattering (TRDLS) has been extensively used to determine the aggregation behavior of diverse nanoparticles in the presence of salts, organic matter, and biological materials (Ntim et al 2012). TRDL was used to investigate the initial aggregation kinetics of f-CNT dispersions which was measured by monitoring the time-dependent increase in hydrodynamic radius (r h ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a recent study on the aggregation of MWNTs as a function of length further confirms the negligible role of length in smaller-diameter MWNT aggregation. [41] The pristine samples possess mean diameter distribution of 0.805±0.243 nm and 0.927±0.274 nm for SG65 and SG76, respectively (Figure S3); the diameter distribution is produced via NIR fluorescence spectroscopy as described earlier. [30] TEM micrographs in Figure 1 show SWNT physical morphology of pristine tubes and SWNTs with surfactant modification.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of MWNT doping concentration on the MWNT size and morphology was reported by Ntim et al where they found that shorter MWNTs show smaller particle aggregates with improved MWNT dispersion as compared to longer MWNTs. [ 27 ] In our study, longer MWNTs were supposed to form larger aggregates, centrifuged out of the composite resin, thus leading to a lower MWNT loading concentration. Therefore, it is expected that shorter MWNTs may result in better dispersion quality and higher loading concentration for the TPP fabrication.…”
Section: It Is Diffi Cult To Develop Tpp-compatible Photoresists Withmentioning
confidence: 98%